Value of exercise and electrical stimulation in the rehabilitation of patients after the knee arthroplasty - Azizov, Mirkhakim; Alimov, Aziz; Shomansurova, Leyla (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Functional outcomes of the total knee arthroplasty is largely dependent on early rehabilitation activities initiated. In patients with flexion contractures of the knee joint before surgeries cases of their incomplete elimination are not uncommon after the total knee arthroplasty. This problem is underrepresented in the scientific literature. There is not enough information on the use of physical methods of therapy, electrical stimulation of the thigh muscles and exercises in patients with above mentioned pathology. Objective: to evaluate the effectiveness of electrical stimulation and exercises with early loading in patients with degenerative- dystrophic changes in knee joint and flexion contracture after the total knee arthroplasty. Material:  outcomes of treatment in 66 women aged from 52 to 73 years with unilateral lesions of knee joint were evaluated. Patients were divided into three groups depending on the clinical tasks and purpose of the rehabilitation period. It was established that the use electrical stimulation of the thigh muscles in conjunction with exercises significantly improved the functional outcomes of total knee arthroplasty in patients with flexion contracture of the knee joint.